A relação ao objeto: um estudo a partir do pensamento de Francisco Suárez - Monticelli, Pedro (2010)
This thesis aims at studying, under the light of contemporary intentionality problems, the relation to the object in the thought of Francisco Suárez. In spite of being a research aiming to explain and connect some passages of the work of that author, the focus is not merely historical, but rather tries to highlight some structural-conceptual aspects which remain up for debate in contemporary notions of intentionality and objectivity.This type of research is justified because it offers clarity about conceptual presuppositions which are not always discussed. In order to bring about such a task within the strict limits of a doctoral thesis, my work has been divided in four stages, which correspond to the four chapters of the thesis. First, I deal with the concept of categorial relation in general. Then I explain the nature of that relation as well as its requisites, with the purpose of showing the quirks of the notion of relation in the Aristotelian tradition. Then, I deal with the relation between reason and being of reason, in general. That is done, on the one hand, to show that the relation to the object is not one of reason, but rather a real relation, and, on the other hand, to show that the relation of reason can be a kind of object. The next step takes on the transcendental relation, given that the relation to the object, according to one of its meanings, is a relation of that kind. Finally, we arrive at the relation to the object according to a second meaning, namely, that of categorial relation of knowledge. As a conclusion, I discuss Suárez s position concerning realist and idealist accounts of knowledge